Success Story Sri Lanka's COVID-19 Response Takes a Different Turn: Healthcare Workers' Burnout Impact - Agung Huda Bayu Anggoro; Elsye Maria Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The COVID-19 pandemic made many countries respond quickly to suppress the transmission of this virus, strict restrictions on the entry of countries were carried out to successfully suppress transmission, Sri Lanka was successful in handling the initial pandemic. However, it lasted for a while, the policy of relaxing social restrictions made the population uncontrollably infected, and limited personnel made the workload and duration of work shift heavy. length of service plays a role in the burnout of Sri Lankan hospital health workers. This study aims to determine the effect of length of service and duration of work shifts on the incidence of Burnout among health workers during the COVID-19 pandemic in Sri Lanka. The method used an Observational Study based on datasets taken crossectional related to the incidence of burnout in health workers during the COVID-19 pandemic in Sri Lankan hospitals. Using the Copenhagen Burnout Inventory (CBI). The results obtained Length of Service has a significant effect on Personal Burnout, Work related burnout, Client related burnout, while the duration of work shifts has a significant effect on work-related burnout, insignificant on Personal Burnout and Client Related Burnout of Health workers in large hospitals in Sri Lanka during the COVID-19 pandemic.